Human Milk–A Valuable Tool in the Early Days of Life of Premature Infants - Ziegler, Ekhard E. (Frontiers in Pediatrics, 2019)
The objective of early premature infant nutrition is to maintain, during the turbulent early days of life, a flow of nutrients that differs only minimally from that which would have prevailed had the infant remained in utero. Out of necessity, nutrients have at first to be provided mainly via the parenteral route. While that is going on, the feeding of small amounts of human milk (gut priming) is initiated as soon as practical. As mother's own milk is not available in sufficient quantity at this time, donor milk needs to be used temporarily. If not available, formula should be used. Gastric residuals are physiologic at this stage and are monitored to guide the increase of the size of feedings. As the volume of milk is gradually increased, nutrient fortification is initiated when the milk volume reaches around 20 ml/kg/day. There is no need to start with less than full-strength fortification. Fortification should employ one of the liquid fortifiers. Adjustable fortification may be employed but is labor-intensive and is not a necessity as long as full feeding volumes of around 170 ml/kg/day are maintained. As the infant grows beyond 1500 g the level of fortification can be reduced gradually by omitting fortification first from one, and then from more feedings. After discharge there is still a need for fortification, which requires the mother to express some of her milk so it can be fortified. Nutrient supplementation directly to the infant would obviate the need for milk expression.